2021
DOI: 10.1590/1982-7849rac2021200253.en
|View full text |Cite
|
Sign up to set email alerts
|

Stay at Home, Casa Porto Delivers: Humanized Entrepreneurship during Pandemic

Abstract: This teaching case describes the trajectory of the entrepreneur Raphael Vidal. The information presented makes it possible to link the history and beliefs of the subject-entrepreneur Raphael to the decisions regarding Casa Porto project in the context of the COVID-19 pandemic. Aspects of his entrepreneurial attitude as a basis for the way he has been conducting Casa Porto are exposed. In addition, elements related to the decision to open, conduct, and maintain a business in situations of crisis are displayed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…In terms of the scientific evidence of entrepreneurship in South America during the COVID-19 pandemic, this systematic review revealed 15 records [111][112][113][114][115][116][117][118][119][121][122][123][124][125]. There were scientific articles that were written in one of three languages: Spanish (5 cases), Portuguese (3 cases), and English (4 cases); but there were also articles with two versions available: in Portuguese and English (3 cases).…”
Section: Discussionmentioning
confidence: 99%
“…In terms of the scientific evidence of entrepreneurship in South America during the COVID-19 pandemic, this systematic review revealed 15 records [111][112][113][114][115][116][117][118][119][121][122][123][124][125]. There were scientific articles that were written in one of three languages: Spanish (5 cases), Portuguese (3 cases), and English (4 cases); but there were also articles with two versions available: in Portuguese and English (3 cases).…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, maybe even seize the moment of reflection to, grounded on the job crafting logic, experiment in a new born-digital business project? Next, in the Casa Porto case (Vinhas & Lopes, 2021), the entrepreneur needs to tighten the belt, reducing costs, while fighting to keep paying the salaries of the team. Finally, the Facile/Ligferv case (Silva, Guimarães, & Castro, 2021) offers an empirical environment to employ the established theories of causation and effectuation to explain the hurdles of an entrepreneur from Minas Gerais, Brazil, that needs to reinvent the business model of an innovative coffee machine to keep performing under the pandemic.…”
Section: Action and Reaction Action And Reactionmentioning
confidence: 99%